2020
DOI: 10.1109/access.2020.3015580
|View full text |Cite
|
Sign up to set email alerts
|

AFAM-PEC: Adaptive Failure Avoidance Tracking Mechanism Using Prediction-Estimation Collaboration

Abstract: During recent years correlation tracking is considered fast and effective by the virtue of circulant structure of the sampling data for learning phase of filter and Fourier domain calculation of correlation. During the occurrence of occlusion, motion blur and out of view movement of target, most of the correlation filter based trackers start to learn using erroneous samples and tracker starts drifting. Currently, adaptive correlation filter based tracking algorithms are being combined with redetection modules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Recent literature shows that researchers are continuously trying to handle tracking failure and redetecting the target after failure. Notable articles relevant to tracking failure detection and avoidance occlusion handling are presented in [5,24] and [25,26], respectively. Discriminative correlation filter trackers also suffer from boundary effects.…”
Section: Related Workmentioning
confidence: 99%
“…Recent literature shows that researchers are continuously trying to handle tracking failure and redetecting the target after failure. Notable articles relevant to tracking failure detection and avoidance occlusion handling are presented in [5,24] and [25,26], respectively. Discriminative correlation filter trackers also suffer from boundary effects.…”
Section: Related Workmentioning
confidence: 99%
“…A Kalman filter is used in various tracking algorithms for occlusion handling [45][46][47][48][49]. Kaur et al [50] suggested a real-time tracking approach using a fractional-gain Kalman filter for nonlinear systems.…”
Section: Related Workmentioning
confidence: 99%
“…Zhou et al [34] proposed an STC learning algorithm with multichannel features and an improved adaptive scheme for scale by using a histogram of oriented gradients feature along with color naming and using kernel methods in the STC framework to improve tracking performance. Khan et al [35] proposed an improved tracking algorithm based on LCT. They incorporated the Kalman filter in the LCT framework for occlusion handling and PSR of the response map for occlusion detection.…”
Section: Related Workmentioning
confidence: 99%